Development of Integrated Welding Jobsheet Production Based Learning in Vocational High School - Rivkih Amanulloh; Budi Santosa; Muhammad Sayuti (Journal of Vocational Education Studies, 2023)
This study aims to analyze the use of integrated welding jobsheets that are usually done at SMK Muhammadiyah 2 Ajibarang. After analyzing and then developing the use of an integrated welding jobsheet commonly used at SMK Muhammadiyah 2 Ajibarang, it becomes an integrated jobsheet that is combined with existing work orders in the industry. The use of the jobsheet was developed to increase the knowledge and competence of students in the Machining Engineering skill competency. This research is research and development (R&D). Stages of research using the design Analysis, Design, Development, Implementation, Evaluation. This research was conducted at SMK Muhammadiyah 2 Ajibarang. The subjects in this study were grade 12 students of Machining Engineering Skills at SMK Muhammadiyah 2 Ajibarang. This study uses a quasi-experimental nonequivalent control group design research method. Collecting data using a questionnaire, pretest, posttest. This study uses expert validators to validate the integrated jobsheet that will be developed, where the average validation result of the three expert validators is 4.25 or 80.5% which can be declared valid. Analysis of research data was done by using the validity of the questionnaire and T-test. To compare the achievement results in the class before being given practical treatment using an integrated worksheet and after being given treatment. We can test this comparison by means of different power testing carried out by pretest and posttest. The result of this research is that the use of integrated welding jobsheet can increase students' knowledge and competence. This study shows an increase in knowledge and competence, after being treated three times by using the use of an integrated worksheet that has been combined with a work order with (Tcount = 11.224 and Sig. = 0.000). The results presented in the form of data analysis are the results of research that has gone through several stages. Integrated jobsheet development research is able to increase students' knowledge and competence of Machining Engineering skills. The Integrated Jobsheet is declared valid to assist the learning process of welding practice in production-based learning in order to increase knowledge and competence.